1983
DOI: 10.1042/bj2120113
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of active Ca2+ uptake by the islet-cell endoplasmic reticulum

Abstract: The possible effects of calmodulin and cyclic AMP on active Ca2+ uptake by the islet-cell endoplasmic reticulum were investigated. Neither calmodulin nor cyclic AMP affected the rate of active Ca2+ uptake, or the steady-state filling capacity of the endoplasmic reticulum when measured in the absence of oxalate. Consistent with these results, calmodulin did not activate the Ca2+-stimulated ATPase activity associated with this cell fraction. During the course of these experiments., it was unexpectedly discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Calcium uptake into sarcoplasmic reticulum [1] and endoplasmic reticulum of various tissues [11,16,20,22,26,33,35,39,44,46,62] can be stimulated by oxalate. This is a characteristic feature of the endoplasmic reticulum, in contrast to calcium uptake into plasma membrane vesicles [30,62], due to the permeability of the endoplasmic reticulum to oxalate.…”
Section: Calcium-precipitating Anionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium uptake into sarcoplasmic reticulum [1] and endoplasmic reticulum of various tissues [11,16,20,22,26,33,35,39,44,46,62] can be stimulated by oxalate. This is a characteristic feature of the endoplasmic reticulum, in contrast to calcium uptake into plasma membrane vesicles [30,62], due to the permeability of the endoplasmic reticulum to oxalate.…”
Section: Calcium-precipitating Anionsmentioning
confidence: 99%
“…Ca 2+ uptake is dependent upon monovalent cations in the endoplasmic reticulum of several tissues [11,22,26,39,40,62], as well as in the sarcoplasmic reticulum [13,17,25,36,37,58]. We have therefore investigated the influence of different cations such as Rb +, K +, Na +, Li + and choline + on nonmitochondrial calcium uptake into leaky isolated cells and in isolated endoplasmic reticulum vesicles prepared from these cells.…”
Section: Monoualent Cationsmentioning
confidence: 99%
“…1 demonstrate an apparent insensitivity of the Ca2 -ATPase toward exogenous Mg2+. Indeed, we [5] and others [3,4] have found that high concentrations of exogenous Mg2 + (required for Ca2 ' uptake) interfere with the detection of Ca2+-ATPase activity. This is due to the high basal Mg'+-ATPase activity present in the microsomal fraction [l -5, 26, 281.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium/calcium countertransport is reported to be inhibited by glucose (Herchuelz, Sener & Malaisse, 1980). The calcium-ATPase is ATP dependent, as is calcium uptake into mitochondria (Sugden & Ashcroft, 1978) and endoplasmic reticulum (Colca et al 1982). So, increasing glucose could increase calcium buffering by any of these ATP-dependent processes.…”
Section: Intracellular Calcium Handlingmentioning
confidence: 99%
“…The steady reduction in intracellular calcium over the recovery period could be due to several cell processes: extrusion from the cell by the cell membrane calcium pump demonstrated in ,-cells (Pershadsingh, McDaniel, Landt, Bry, Lacy & McDonald, 1980); an increase in the sodium/calcium exchange that exists in f8-cells (Herchuelz, Sener & Malaisse, 1980) due to restoration of the sodium gradient and the rise in intracellular calcium; and/or uptake into cell organelles such as mitochondria (Sugden & Ashcroft, 1978), endoplasmic reticulum (Colca, McDonald, Kotagal, Patke, Fink, Greider, Lacy & McDaniel, 1982) and secretory granules (Abrahamsson, Gylfe & Hellman, 1981).…”
Section: Intracellular Calcium Handlingmentioning
confidence: 99%